RESPONSE GROWTH AND PRODUCTION OF LETTUCE (Lactuca sativa L.) AGAINST GIVING OF ORGANIC FERTILIZER - FITRI CANDRA; ACHMAD MULYADI; MAULIDI SP (Fakultas Pertanian Universitas Tanjungpura, 2018)
This reseach aims to determine the response growth and production of lettuce against giving of organic fertilizer. This reseach using the design of random group with the treatment dose of organic fertilizer : without organic fertilizer, dose of 10% organic fertilizer/polybag, dose of 12% organic fertilizer/polybag, dose of 14% organic fertilizer/polybag, dose of 16% organic fertilizer/ polybag, dose of 18% organic fertilizer/polybag. The results of research suggests that giving organic fertilizer can increase growth and production of lettuce. Organic fertilizer with dose of 16% organic fertilizer/polybag giving root volume, number of leaves, weight of dry economically, weight of fresh economically.Keywords : lettuce, organic fertilizer, growth, production